Silicon mechanical sensors for cryogenic temperatures: experimental simulation and characterization - Druzhinin, A.; Maryamova, 1.; Kutrakov, О.; Pavlovskyy, I.; Palewski, Т. (Видавництво Національного університету "Львівська політехніка", 2004)
Temperature dependencies of Seebeck coefficient for free and strained heavily doped Si- Ge whiskers were studied in temperature range 4,2-300K. A compressive strain was shown to substantially change temperature behaviour of Seebeck coefficient. The main peculiarity of such change is stability of Seebeck coefficient in a wide temperature range 10-100 K, that is prospec¬tive for the whisker application in sensors of cryogen temperatures. Sensors for measurement of cryogenic temperatures operating in high magnetic field on the base of the whiskers were designed. Simplified circuit diagrams of processing the signals from the sensors were presented.